Intracoronary delivery of bone marrow cells to the acutely infarcted myocardium. Optimization of the delivery technique - Meluzín, Jaroslav; Vlasín, Michal; Groch, Ladislav; Mayer, Jirí; Kren, Leos; Rauser, Petr; Tichý, Boris; Hornácek, Ivan; Sitar, Jan; Palsa, Stanislav; Klabusay, Martin; Korístek, Zdenek; et al. (Cardiology, 2009)
OBJECTIVES: Intracoronary cell transplantation during catheter balloon inflations may be associated with adverse events. We studied the effectiveness of an alternative transplantation technique--intracoronary cell infusion. METHODS: Fourteen pigs, which had survived acute myocardial infarction, were randomized into 2 treatment groups and 2 controls. Three days after infarction, 12 pigs underwent allogeneic intracoronary mononuclear bone marrow cell transplantation using either the standard technique (short-term cell injections during repeat balloon inflations, technique A, n = 6) or continuous intracoronary cell infusion without balloon inflations (technique B, n = 6). Implanted cells were stained with fluorescent dye. After transplantation, the pigs were euthanized and myocardial samples were analyzed by fluorescent microscopy. RESULTS: The mean numbers of fluorescently labeled bone marrow cells in the infarction border zone, in the infarction mid-area and in the center of myocardial infarction were 84, 72 and 55 using technique A, and 29, 57 and 46 using technique B, respectively. The mean cell retention in the infarction border zone of 84 cells for technique A and 29 cells for technique B differed significantly (p = 0.034, two-tailed t test). CONCLUSION: The continuous intracoronary cell infusion technique is a less efficient cell delivery technique as compared with the standard technique using repeat intracoronary balloon inflations.
Keywords: Animals; Female; Fluorescent Dyes; Microscopy, Fluorescence; Fluoresceins; ženské pohlaví; Cardiac Catheterization; katetrizace; prasata; fluorescenční barviva; fluorescenční mikroskopie; transplantace kostní dřeně; Male; modely nemocí na zvířatech; Swine; fluoresceiny; Disease Models, Animal; Myocardial Infarction; Bone Marrow Transplantation; Catheterization; srdeční katetrizace; zvířata; mužské pohlaví; infarkt myokardu